Cost of using power reapers: Malaysian experience - Aribi, Kamarudzaman; Md. Salleh, Yaacob (Farm Machinery Industrial Research Corp., 1988)
Field data on the repair and ownership costs of power reapers are presented. The power reapers were used for general purpose work like grass mowing and hedge trimming. The curves obtained in the study show the minimum of total accumulated cost ownership at 1200 accumulated usage hours and the wear out life at 2600 accumulated usage hours. Depreciation and repair costs were approximately 15% of the total cost of operation.